A Novel Alkaliphilic Streptomyces Inhibits ESKAPE Pathogens - Terra, Luciana; Dyson, Paul J.; Hitchings, Matthew D.; Thomas, Liam; Abdelhameed, Alyaa; Banat, Ibrahim M.; Gazze, Salvatore A.; Vujaklija, Dušica; Facey, Paul D.; Francis, Lewis W.; Quinn, Gerry A. (Frontiers in Microbiology, 2018)
In an effort to stem the rising tide of multi-resistant bacteria, researchers have turned to niche environments in the hope of discovering new varieties of antibiotics. We investigated an ethnopharmacological (cure) from an alkaline/radon soil in the area of Boho, in the Fermanagh Scarplands (N. Ireland) for the presence of Streptomyces, a well-known producer of antibiotics. From this soil we isolated a novel (closest relative 57% of genome relatedness) Streptomyces sp. capable of growth at high alkaline pH (10.5) and tolerant of gamma radiation to 4 kGy. Genomic sequencing identified many alkaline tolerance (antiporter/multi resistance) genes compared to S. coelicolor M145 (at 3:1), hence we designated the strain Streptomyces sp. myrophorea, isolate McG1, from the Greek, myro (fragrance) and phorea (porter/carrier). In vitro tests demonstrated the ability of the Streptomyces sp. myrophorea, isolate McG1 to inhibit the growth of many strains of ESKAPE pathogens; most notably carbapenem resistant Acinetobacter baumanii (a critical pathogen on the WHO priority list of antibiotic resistant bacteria), vancomycin resistant Enterococcus faecium, and methicillin resistant Staphylococcus aureus (both listed as high priority pathogens). Further in silico prediction of antimicrobial potential of Streptomyces sp. myrophorea, isolate McG1 by antiSMASH and RAST software identified many secondary metabolite and toxicity resistance gene clusters (45 and 27 respectively) as well as many antibiotic resistance genes potentially related to antibiotic production. Follow-up in vitro tests show that the Streptomyces sp. myrophorea, isolate McG1 was resistant to 28 out of 36 clinical antibiotics. Although not a comprehensive analysis, we think that some of the Boho soils’ reputed curative properties may be linked to the ability of Streptomyces sp. myrophorea, isolate McG1 to inhibit ESKAPE pathogens. More importantly, further analysis may elucidate other key components that could alleviate the tide of multi-resistant nosocomial infections.